The Role of Executive Function in Developmental Stuttering - Anderson, Julie D.; Ofoe, Levi C. (Seminars in Speech and Language, 2019)
Developmental stuttering is a complex disorder and children who stutter form a heterogeneous group. Most contemporary researchers would agree that multiple factors, including those associated with linguistic, motor, sensory, and emotional processes, are likely involved in its development and/or maintenance. There is growing evidence, however, that cognitive processes also play a role. In this article, we briefly review behavioral and parent-report studies of executive function in children who stutter, the findings of which have generally suggested that these skills may be challenging for at least some children who stutter. We then consider how deficits in executive function could provide an explanatory account for not only the multifactorial nature of developmental stuttering but also the considerable amount of variability that exists among individuals who stutter.
Keywords: executive function; stuttering; fluency disorders; memory; inhibition; flexibility